Dispute at the Table: Reflections on the Incident in Antioch (Gal 2,11–14) in Light of the Bylaws of Ancient Collegia - Popa, Romeo (Zeitschrift für die neutestamentliche Wissenschaft, 2025)
In this article, the consequential dispute with Kephas in Antioch, as Paul relates it in Gal 2,11-14, is examined primarily in the light of the language of the documentary papyri and inscriptions. The focus is not on theological or chronological questions, but - from a reader-oriented perspective - on the way the narrative might have been received by the addressees of the letter. The bylaws of selected ancient associations with various measures against inappropriate behavior during meetings serve to place the incident in the appropriate cultural context. With regard to the divisions caused by Kephas and Paul’s fierce reaction, the question is asked whether the pragmatic intention of the author and the reception on the part of the addressees necessarily corresponded or whether a more complex communication situation should be assumed.